Primary Amyloidosis Manifesting as Cholestatic Jaundice after Laparoscopic Cholecystectomy. (7th June 2015) - Misiakos, Evangelos P.; Bagias, George; Tiniakos, Dina; Roditis, Konstantinos; Zavras, Nick; Papanikolaou, Ioannis; Tsirigotis, Panagiotis; Liakakos, Theodore; Machairas, Anastasios
Abstract : A 71-year-old female patient with cholelithiasis who had undergone laparoscopic cholecystectomy was admitted with obstructive jaundice (total bilirubin 6 mg/dL) three months later. An ERCP was performed, in which a gallstone was found, followed by a sphincterotomy and cleansing of the bile duct. Due to deterioration of jaundice (>25 mg/dL), a new, unsuccessful ERCP and stent placement was carried out. Because of ongoing cardiac failure, she underwent an echocardiogram which revealed restrictive cardiomyopathy possibly due to amyloidosis. A liver biopsy was performed, which was positive for amyloid deposits in the liver, and the diagnosis was confirmed by the detection of monoclonal λ IgG protein in urine. The patient's jaundice gradually deteriorated and she died one week later from hepatic insufficiency.